Gut Akkermansia enhances liver protection and facilitates copper removal during D-penicillamine treatment in a Wilson’s disease model - Xi Huang; Yanqi Jin; Tianyuan Wang; Danting Fu; Jindi Ma; Xiaopeng Yu; Yingfeng Lu; Jingyuan Song; Yu Chen; Ren Yan; Yimin Zhang (Microbiology Spectrum)
ABSTRACT Patients afflicted with Wilson’s disease (WD) may encounter hepatic and extraneous manifestations due to the progressive accumulation of copper in the liver and other subsequent organs. Copper-chelating agents, such as D-penicillamine (DPA), are commonly utilized in the medical treatment of copper overload in WD. Manipulating the composition of gut microbiota appropriately can enhance drug efficacy and safety. This study aims to investigate how targeted intervention on gut microbiota influences the effectiveness of copper removal in a WD model during DPA treatment. First, following a 4-week treatment of DPA, the liver copper concentration and gut microbial composition were assessed in the WD mice model to identify potential candidates for targeted regulation of gut microbiota. Second, after 8 weeks of manipulating the gut microbiota during DPA treatment, various parameters including blood liver function indicators, tissue copper load, hepatic histopathological features, and gut microbiota were investigated in WD mice. The findings demonstrated that the presence of Akkermansia significantly enhances the efficacy of DPA, leading to a more efficient elimination of copper from tissues and a greater improvement in liver injury, liver dysfunction, and gut dysbiosis. In contrast, Butyricimonas has an antagonistic effect. The results of gene function prediction analysis indicated that the altered gut microbial function by DPA and Akk is primarily linked to energy generation/utilization, amino acid, fatty acid, lipid, and nucleic acid metabolisms. To summarize, this study provides experimental evidence for the potential application of targeted regulation of gut microbiota in the adjunctive therapy of copper dysregulation disease.IMPORTANCECopper is an essential element in virtually all living organisms. Wilson’s disease (WD) is a representative disorder caused by the disruption of copper homeostasis. Oral-chelating agents are the first-line treatment for copper-overloaded diseases, with D-penicillamine (DPA) being the prototypical drug. However, the efficacy and adverse effects of DPA remain challenging in its use for WD treatment. In our study, the supplementation of Akkermansia muciniphila (Akk), a key gut microbe, along with DPA was demonstrated to enhance copper removal, ameliorate liver injury and dysfunction, and restore gut dysbiosis in a mouse model of WD. These findings highlight the significant potential applications of targeted modulation of gut microbiota as “pharmacomicrobiomics” in adjunctive therapy for disorders involving copper dysregulation.